The mitochondrial genome of Diostracus lamellatus (Diptera: Dolichopodidae) - Qilemoge; Shang Gao; Chufei Tang; Ning Wang; Ding Yang (Mitochondrial DNA. Part B. Resources, 2018)
The long-legged fly Diostracus lamellatus Wei et Liu belongs to the subfamily Hydrophorinae of Dolichopodidae. The mitogenome of D. lamellatus was sequenced, the first representative of the mitogenome of the subfamily. The mitogenome is 14,143 bp totally, consisting of 13 protein-coding genes, two rRNAs, and 22 transfer RNAs. All genes have the similar locations and strands with that of other published species of Dolichopodidae. The nucleotide composition biases towards A and T, which together made up 75.8% of the entirety. Bayesian inference analysis strongly supported the monophyly of Dolichopodidae. It suggested that the Hydrophorinae is the sister group to the clade of Sciapodinae + Dolichopodinae.